2023
DOI: 10.1021/acscatal.2c06299
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Surface Charge Localization Over Nitrogen-Doped In2O3 for CO2 Hydrogenation to Methanol with Improved Stability

Abstract: Indium oxide (In 2 O 3 ) is active and promising for selective hydrogenation of CO 2 to methanol. However, it suffers from over-reduction at elevated temperatures, causing deactivation. Herein, a nitrogen-doped In 2 O 3 (N−In 2 O 3 ) catalyst was prepared using a plasma-intensified nitrogen-doping technology. It is confirmed that nitrogen doping is effective for the stabilization of In 2 O 3 . The doped nitrogen enhances the surface charge localization, which inhibits the over-reduction on the oxide surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…It can be concluded that the Fe 3 /MoS 2−v catalyst exhibits significantly higher TOFs of CH 3 OH production than CH 4 formation at all temperature and pressure ranges. Specifically, the TOF of CH 3 OH formation on Fe 3 /MoS 2−v at 4 MPa and 523 K can achieve 1.6 × 10 −4 s −1 site −1 , close to the experimental TOF values of metal oxide catalysts,53,54 while the TOF of CH 4 on this site is only 1.3 × 10 −11 s −1 site −1 . By calculating the degree of rate control (DRC) of reaction intermediates and transition states (FigureS8),55 we find that the removal of the hydroxyl intermediate and *H 2 COO hydrogenation is vital to the overall reaction rate.…”
supporting
confidence: 78%
“…It can be concluded that the Fe 3 /MoS 2−v catalyst exhibits significantly higher TOFs of CH 3 OH production than CH 4 formation at all temperature and pressure ranges. Specifically, the TOF of CH 3 OH formation on Fe 3 /MoS 2−v at 4 MPa and 523 K can achieve 1.6 × 10 −4 s −1 site −1 , close to the experimental TOF values of metal oxide catalysts,53,54 while the TOF of CH 4 on this site is only 1.3 × 10 −11 s −1 site −1 . By calculating the degree of rate control (DRC) of reaction intermediates and transition states (FigureS8),55 we find that the removal of the hydroxyl intermediate and *H 2 COO hydrogenation is vital to the overall reaction rate.…”
supporting
confidence: 78%
“…These results were in agreement with the CO 2 -TPD results that the temperature of CO 2 desorption peak at higher temperature shifted from 568 °C for ZnZrO x to 619 °C for 10In 2 O 3 -ZnZrO x . Therefore, compared with the formed oxygen vacancies on ZnZrO x by the doping of Zn atoms into ZrO 2 , 10In 2 O 3 -ZnZrO x not only possessed more oxygen vacancies (Figure (d) and Table ) due to the formation of defect on In 2 O 3 lattice and partial reduction of In 2 O 3 under reaction conditions but also enhanced the adsorption and activation ability of CO 2 , which will increase reaction activity of CO 2 during its hydrogenation conversion process.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in panels a–c of Figure , the O 1s peak includes three peaks on all of the In 2 O 3 catalysts. These peaks located at 529.6, 530.9, and 531.8 eV are assigned to lattice oxygen (O lattice ), defective oxygen sites (O defect ), and hydroxyl groups (OH) absorbed on the surface (i.e., H 2 O and CH 3 OH), respectively . To further study the evolution of the surface oxygen vacancies, their relative concentration was calculated by C Odefect = A Odefect /( A Odefect + A Olattice ). , The results are shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%